RELATIONSHIP BETWEEN AGE AND RED-S OR FEMALE ATHLETE TRIAD RISK LEVEL. Issue 3 (31st March 2019) - Holtzman, Bryan; Whitney, Kristin E.; Parziale, Allyson; Ackerman, Kathryn E.
RELATIONSHIP BETWEEN AGE AND RED-S OR FEMALE ATHLETE TRIAD RISK LEVEL BACKGROUND: Relative energy deficiency in sport (RED-S) is a term recently introduced by the International Olympic Committee that describes the constellation of health and performance consequences experienced by athletes resulting from inadequate energy availability (EA). RED-S includes the clinical features described by the well-established Female Athlete Triad (the interrelationship of low EA, menstrual dysfunction, and low bone mineral density (BMD)) and highlights the broad multiplicity of health implications resulting from a low energy state. Both the RED-S and Triad models have proposed risk assessments models and return to play (RTP) pathways. Clinically, the effects of low EA may take time to manifest, so a greater percent of older athletes may be at risk compared to their younger counterparts. The purpose of this study was to investigate how RED-S and Triad risk level varies with age in a pediatric/adolescent population. We hypothesized that a greater percent of older athletes would be at higher risk levels than younger athletes. METHODS: One-thousand female athletes presenting to a sports medicine clinic completed a 476 item survey with questions pertaining to sport, nutrition, family history, and various health aspects. Athletes were split into age groups based on their most recent birthday and athletes age 15–19 were included in this study. Retrospective chart review was used to assess diagnostic measures, such as BMD as measured by dual-energy x-ray absorptiometry (DXA). RED-S risk was assessed using our understanding of the RED-S Clinical Assessment Tool (RED-S CAT) and Triad risk was assessed using the Triad Cumulative Risk Assessment (Triad CRA). Both systems categorize athletes into low, moderate, or high risk, and in some cases, we considered "risk" to be anyone at moderate or high risk for each syndrome. Chi-squared tests were used to determine associations between risk and age and simple linear regression was used to determine the relationship between age and risk. Proportion Z-scores were used to determined prevalence differences between RED-S and Triad. Significance was determined at p<0.05. RESULTS: Of the 1000 athletes who completed the survey, 708 (70.8%) were in our age range of interest. Of those 708, 24.34% were 15, 23.40% were 16, 23.00% were 17, 16.96% were 18, and 12.30% were 19 years old. DXA scans were available for 19.4% of the sample: 21.6% of 15 year olds, 16.3% of 16 year olds, 24.8% of 17 year olds, 20.0% of 18 year olds, and 9.5% of 19 year olds. Age was associated with risk for RED-S and Triad when risk was stratified (p=0.0015 and p=0.0057) and binary (p=0.0078 and p=0.0208). When grouping moderate and high risk groups together, a positive linear relationship was observed between age and percentage of athletes at risk for RED-S (p<0.05). This relationship was not observed for Triad risk (p>0.10). A trend was observed between age and high Triad risk, but this relationship did not reach statistical significance (p=0.0646). More athletes were at risk for RED-S using the RED-S CAT (83.4%) than Triad using the Triad CRA (59.0%, p<0.0001). This observation was true for each age (p<0.001). The prevalence of each risk level at each age for RED-S and Triad, using their respective tools, are shown in Table 1. CONCLUSION/SIGNIFICANCE: Age may modulate the risk of RED-S and Triad as more time accumulates in a low energy state and/or more societal and sport-related influences make individuals susceptible to RED-S/Triad. Early detection of risk factors for RED-S and Triad is essential for preventing the progression of energy deficiency. Additionally, the RED-S CAT consistently identified more athletes as "at-risk" for inadequate EA than the Triad CRA; if these were used for clinical screening (such as in a preparticipation setting), the RED-S CAT would flag more athletes for further medical attention. TABLES/FIGURES: Table 1. Risk for RED-S and Triad at each age. RED-S Risk Triad Risk Age Low Moderate High Low Moderate High 15 22.80% 64.30% 12.90% 42.70% 52.00% 5.30% 16 15.70% 74.20% 10.10% 44.40% 53.40% 2.20% 17 19.40% 72.70% 7.90% 46.70% 47.30% 6.10% 18 10.90% 69.10% 20.00% 34.50% 54.50% 10.90% 19 7.10% 72.60% 20.20% 27.40% 60.70% 11.90%